Direct subphthalocyanine conjugation to bombesin vs. indirect conjugation to its lipidic nanocarrier. Issue 19 (21st April 2016) - Bernhard, Yann; Gigot, Elodie; Goncalves, Victor; Moreau, Mathieu; Sok, Nicolas; Richard, Philippe; Decréau, Richard A.
Abstract : Azido-liposomes give fluorophores/contrast agents with no reactive functional group available on their backbone a second chance to be (indirectly) bioconjugated (with bombesin). Abstract : Bombesin (BBN) was covalently bound to graftable subphthalocyanine (SubPc) or to a cholesterol derivative, a component of a liposome that encapsulates non-graftable SubPc. The latter bioconjugation approach was suitable to address the stability of SubPc and was achieved by copper-free click-chemistry on the outer-face of the liposome. Liposomes were purified (FPLC) and then analyzed in size (outer diameter about 60 nm measured by DLS). In vitro binding studies allowed to determine the IC50 13.9 nM for one component of the liposome, cholesterol, conjugated to BBN. Hence, azido- (or alkynyl-) liposomes give fluorophores with no reactive functional group available on their backbone a second chance to be (indirectly) bioconjugated (with bombesin).